Dirichlet Averages of Generalized Multi-index Mittag-Leffler Functions - R.K. Saxena; T.K. Pogany; J. Ram; J. Daiya (National Academy of Sciences of Armenia)
The object of this article is to investigate the Dirichlet averages of the generalized multi--index Mittag--Leffler functions introduced by Saxena and Nishimoto \cite{23, 24}. Representations of such relations are obtained in terms of Riemann--Liouville integrals and hypergeometric functions of several variables. Some interesting special cases of the established results associated with generalized Mittag--Leffler functions due to Srivastava and Tomovski \cite{28} and multi--index Mittag--Leffler functions due to Kiryakova \cite{13} are deduced. Certain results given earlier by Kilbas {\em et al.} \cite{9} also follow as special cases of our findings.
Keywords: Mathematics